2017
DOI: 10.1136/bmjopen-2016-013242
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the methodological quality of controlled trials evaluating Chinese herbal medicine in patients with rheumatoid arthritis

Abstract: ObjectivesWe appraised the methodological and reporting quality of randomised controlled clinical trials (RCTs) evaluating the efficacy and safety of Chinese herbal medicine (CHM) in patients with rheumatoid arthritis (RA).DesignFor this systematic review, electronic databases were searched from inception until June 2015. The search was limited to humans and non-case report studies, but was not limited by language, year of publication or type of publication. Two independent reviewers selected RCTs, evaluating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…4 [ 29 ]. It was observed that adherence to recommended reporting guidelines was suboptimal in the included clinical papers of this review, similar to previous findings of systematic reviews assessing the reporting quality of herbal trials [ 83 , 84 ]. There is insufficient reporting on the chemical fingerprinting and qualitative evaluation of phytochemical composition or other foreign materials, e.g., pesticide in most randomised controlled and quasiexperimental trials.…”
Section: Discussionsupporting
confidence: 82%
“…4 [ 29 ]. It was observed that adherence to recommended reporting guidelines was suboptimal in the included clinical papers of this review, similar to previous findings of systematic reviews assessing the reporting quality of herbal trials [ 83 , 84 ]. There is insufficient reporting on the chemical fingerprinting and qualitative evaluation of phytochemical composition or other foreign materials, e.g., pesticide in most randomised controlled and quasiexperimental trials.…”
Section: Discussionsupporting
confidence: 82%
“…For many years, Chinese herbal medicine has been administered for RA treatment [ 6 , 7 ]. Combinations of various medications such as oral Chinese herbal decoctions, prescription preparations, and external applications have attracted interest in recent years as they have diverse applications [ 8 – 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are few studies on it, and it is an effective way to treat RA in the future [18,19]. Sinomenine and other plants Chinese herbal medicine have been found to inhibit RA, which is the main treatment of traditional Chinese medicine at present, which can effectively relieve the pain and swelling caused by RA, but also has the advantages of low price and less adverse reactions, so it is the focus of clinical research [20,21].…”
Section: Introductionmentioning
confidence: 99%